Progressivism in the implementation of the MBKM curriculum as a digital transformation of islamic elementary education institutions (Asian Journal of Educational Technology, 2022)
Education is a process to humanize humans. The development of education is undergoing rapid changes in Indonesia due to the impact of COVID-19 and MBKM policies. It is at this time that digital transformation in education is running fast, it requires the readiness of educational institutions, teachers, students, and parents. This study aims to analyze the digital transformation of Islamic educational institutions in responding to the MBKM curriculum with the paradigm of Progressivism. This study uses a literature review as a method. Data was obtained from observations and interviews of researchers with several managers of Islamic higher education institutions in Ponorogo. The data that has been obtained were analyzed with the perspective of John Dewey's Progressivism education theory in his book Education of democracy. The results showed that Islamic educational institutions in Ponorogo quickly responded to changes in the education model with digital transformation so that they could implement the MBKM curriculum implemented in Islamic educational institutions under the Ministry of Religion of the Republic of Indonesia. From the perspective of the educational flow of John Dewey's progressivism in education, the learning process of students must be given the freedom to express opinions. Students must be active and not just accept the knowledge given by the teacher. Likewise, the teacher must create an atmosphere so that students always feel thirsty for knowledge. Managers of educational institutions must also understand how education is carried out. Education managed by people who do not understand the problem of education will hinder education itself and the manager of educational institutions must be progressive in making policies because the development of education is always dynamic.